Two new species of eumenine wasps in the genus Zethus Fabricius (Hymenoptera, Vespidae, Eumeninae) from the New World - Hermes, Marcel G. (Zootaxa, 2012)
Zethus (Zethus) caetetus sp. nov. (Brazil) and Zethus (Zethus) flaviventris sp. nov. (Costa Rica) are described and figured.Both species belong to the Z. heydeni species group. A total of 218 species of Zethus are currently recognized for the Americas.